Current available therapies and future directions in the treatment of malignant gliomas - Annick Desjardins (Dove Medical Press, 2008)
Annick Desjardins1,2, David A Reardon1,3, James J Vredenburgh1,21The Preston Robert Tisch Brain Tumor Center; 2Department of Medicine; 3Department of Surgery, Duke University Medical Center, Durham, NC, USAAbstract: The prognosis of patients diagnosed with malignant glioma (MG) remains poor. However, recent advances in neuro-oncology allowing a better understanding of this particular disease have allowed the development of new therapeutics. Many molecular genetic and signal transduction pathway targets have been identified that are now being investigated. Novel locoregional treatments, as well as strategies to improve regional delivery, are being evaluated. Studies of combinations of these approaches are also underway. In this review, we will discuss the current and future therapies under evaluation for the treatment of malignant gliomas.Keywords: glioma, glioblastoma, targeted therapy, kinase inhibitor